Clinical Presentation and Management of Mesenteric Cystic Masses In Children: A Six-Year Single-Center Analysis in Bangladesh - Md Sharif Imam; Mozammel Hoque; Kamrun Laila; Md Tameem Shafayat Chowdhury (Journal of Chittagong Medical College Teachers' Association, 2026)
Background: Mesenteric cysts are intra-abdominal masses found in children, mainly caused by embryonic defects in the development of the lymphatic system. This study aims to evaluate the clinical findings, management strategies, and outcomes associated with mesenteric cysts at our institution. Materials and methods: This prospective observational study involved 27 pediatric patients who underwent surgery for mesenteric cysts at the Department of Pediatric Surgery of Chattagram Maa-O-Shishu Hospital Medical College between January 2019 and December 2024. We assessed clinical findings, radiological investigations, surgical procedures, histopathological evaluations, postoperative complications, and follow-up data. All data were collected prospectively. Results: The median age at diagnosis was 5.25 years, with a female-to-male ratio of 1.45:1. The most common clinical manifestations were abdominal pain (70.4%) followed by a palpable abdominal mass (55.5%) and vomiting (25.9%). The jejunal mesentery (55.5%) was the most common site of origin for mesenteric cysts, followed by the ileal mesentery (33.3%) and 11.2% originated from the sigmoid mesentery. The median size of the mesenteric cystic mass was 8.6 ± 4.4 cm. Complete and successful removal of the mesenteric cysts was achieved in all cases. Surgical management included enucleation (n =17) cyst excision combined with bowel resections and primary intestinal anastomosis (n =8) and laparoscopic resection of the cyst (n = 2). Early post-operative complications included only wound site infections in three (11.1%) patients. Histologically, simple cyst with mesenteric lymphangiomas was detected in 19 cases and mesotheliomas in 6 cases. None of the patients experienced a recurrence of their condition. Conclusions: The most common presenting symptom of a mesenteric cyst was abdominal pain. Jejunal mesentery was the commonest site. The relationships between the mesenteric cyst and adjacent organs largely influence the surgical approach. JCMCTA 2026 ; 37 (1) : 152-157